4 - week alternate : day fasting in young overweight / obese males on body composition & health indices - Sim, Da Wei (2018)
Background: Alternate – day fasting (ADF), when performed over 8 – 12 weeks has been shown to induce weight loss and improve several health markers. However, it remains to be seen whether 4 weeks is enough to see any significant changes in body weight, body composition and health indices, such as resting blood pressure (BP) and fasting blood glucose (BG). Purpose: To investigate if 4 weeks of ADF can reduce body weight, improve body composition and health indices in young, overweight and obese males. Methods: Thirteen healthy young men with a body mass index of ≥ 23kg/m2 participated in this 4 – week ADF study. They visited the lab for five times; before, after and at weekly intervals during the 4 weeks of ADF. Body composition was measured twice, before and after the ADF regime. During each visit, their body mass, resting blood pressure, fasting blood glucose and weekly physical activity level were also measured. Fasting day dietary recall was also collected during each week of the ADF. Results: Significant reductions in body mass, BMI, fat mass (p < 0.001) and percentage body fat (p = 0.002) was observed without a significant reduction in FFM. Resting BP and fasting BG after ADF was not significantly different after the 4 – week ADF regime. Physical activity level remained constant throughout the study. Conclusions: 4 weeks of ADF can induce significant reduction in body weight through decreased fat mass, while maintaining FFM in healthy, overweight males.